FINAL PIT PLANNING COAL MINING IN 16 PHASE 2 SEAMS IN PT. KTC COAL MINING & ENERGY, KECAMATAN. PALARAN, SAMARINDA, EAST KALIMANTAN - Ahmad Fauzan Haryono (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2019)
Mining stage design which is a complex problem in terms of three-dimensional geometry that is always changing, then in this thesis the pit limit, mine sequence design or mining stages are in accordance with the tolerance stripping ratio recommended by the company and the production equipment to be used in order to obtain production targets the optimal. The research was conducted using software to design the final pit and block model method to calculate the volume. The results of the research that have been carried out obtained 752,930 MT of mined reserves and Over Burden (OB) volumes of 4,439,394 BCM and Stripping Ratio (SR).